MODERN PEDAGOGICAL TECHNIQUES: INTERACTIVE TEACHING METHODS AND THEIR ADVANTAGES - Utanov Utkir Kurbonovich; Esanov Abdulatif Sherali O‘g‘li (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study aims to examine the role of parent-teacher cooperation in enhancing student development, focusing on how effective communication, parental involvement, and high levels of collaboration positively impact students' academic and personal growth. Methods: A qualitative approach was used, involving 200 participants, including teachers, parents, and students. Data were collected through surveys, interviews, and focus group discussions. Thematic analysis and basic statistical methods were applied to analyze the data, with ethical considerations prioritized throughout. Results: The study found that targeted communication between parents and teachers significantly improved students' academic success and personal development. Parental involvement in the educational process led to better academic performance, enhanced social skills, and a positive attitude toward school. High levels of cooperation resulted in improved academic achievement and strengthened personal and social skills in students. Novelty: This study highlights the importance of structured parent-teacher partnerships, offering insights into how effective communication and involvement can foster not only academic success but also the holistic development of students, contributing to improved education within communities.